Impact of front-of-pack labels with nutrition and Grass-Fed claims on consumer perceptions and expected sensory and nutritional characteristics of Cheddar cheese – A comparative study of Irish and US consumers. (October 2022) - McGuinness, Lauren; McCabe, Mairead; Kiernan, Celine; McCrickerd, Keri; Forde, Ciaran G.; Dolores O'Riordan, E.; Feeney, Emma L.
Highlights: US and Irish consumers completed an online Front-of-Pack cheese label survey. Consumers rated expected characteristics and took part in a portion selection task. Inclusion of Grass-Fed on label did not influence sensory expectations of cheese. Grass-fed on label increased perceived healthiness and naturalness of cheese. A Lighter Fat claim negatively affected sensory expectations. Abstract: Consumer interest in Grass-Fed dairy products is increasing with some consumer groups willing to pay a premium for dairy labelled as Grass-Fed. The aim of this study was to examine the effect of the term Grass-Fed on a label in combination with claims on fat content, on consumer perceptions of Cheddar cheese in Irish and US participants. Consumers from Ireland (n = 345) and the United States (n = 432) completed an anonymous online survey and were presented with one of two sets of cheese label images, either Regular-Fat and Regular-Fat-Grass-Fed or Lighter-Fat and Lighter-Fat-Grass-Fed. Participants were asked to rate expected sensory characteristics and perceived healthiness and naturalness, based on each label. Participants then selected a portion of each cheese that they would be likely to consume on a slice of toast for lunch, from 100 portion size images ranging from 1.2 g to 120 g. Inclusion of a Grass-Fed claim on a cheese label did not influence sensory expectations of cheese, but perceived healthiness and naturalness were higher, in both cohorts. The Lighter-Fat claim had a negative influence on sensory expectations, with consumers in both cohorts reporting a lower expected liking and flavour intensity. In the Irish cohort, a Lighter-Fat claim enhanced perceived healthiness. The front-of-pack claim had no impact on portion selection in US consumers. Irish consumers, however, chose a larger portion for the Lighter-Fat cheese compared to the Regular-Fat-Grass-Fed cheese. Inclusion of Grass-Fed on the label alongside information on Regular-Fat or Lighter-Fat may enhance consumers' perceptions of healthiness and naturalness, without compromising sensory expectations. Products with Lighter labels may be chosen in larger portions, with potential implications for consumers who choose them as part of a weight-control strategy.